Strategies of international fiscal competition for foreign direct investment in a model with impure public inputs - Christoph Sauer; Margit Schratzenstaller (Georg-August-Universität Göttingen, Volkswirtschaftliches Seminar, 2002)
This paper concentrates on international fiscal competition for internationally mobile direct investment. We differentiate between multinational enterprises whose direct investments are internationally mobile and domestic enterprises whose investment activities are limited to their country of residence. In a model with impure public inputs we analyse strategies of tax competition and examine the effects of competition by government expenditures for public inputs under the assumption that preferences for public inputs are different for each type of firms.
Keywords: 330; Steuerwettbewerb; Finanzpolitik; Standortwettbewerb; Direktinvestition; Zwei-Länder-Modell; Öffentliches Gut; Bottleneck; Theorie